Peer sexual harassment and peer violence: South African children at risk - Fineran, S; Bennett, L; Sacco, T (Social Work/Maatskaplike Werk, 2001)
This paper reports on a 1997 study of peer sexual harassment and peer violence in a sample of 261 South African adolescents age 14 to 18. Seventy-nine percent of South African students report experiencing some form of sexual harassment by peers and 78% of South African students report perpetrating sexual harassment to peers at school. Girls were found to experience a higher frequency of sexual harassment and physical violence than boys. A power scale measuring male dominance indicated that boys scored significantly higher than girls on the endorsement of male social role power and perpetrated significantly more sexual harassment and physically and sexually iolent behaviours than girls. Girls found the experience of sexual harassment, physical violence and sexual violence to be significantly more threatening than boys. With regard to peer relationships, girls report experiencing significantly more sexual harassment from peers they did not know and peers whom they had dated than did boys. Similarly, girls also reported experiencing significantly more physical violence and sexual violence from peers they had dated. The advent of major social change in South Africa affords an opportunity to study students from this diverse culture with regard to their experience of peer sexual harassment and peer violence in school. This paper reports on peer sexual harassment, physical and sexual violence in a sample of 261 South African adolescents age 14 to 18. This report is based on data collected in a 1997 study of peer sexual harassment af!.d peer violence among South African high school students. For the purposes of thi study peer sexual harassment is defined as unwanted or unwelcome behaviours, such as making sexual comments, jokes, gestures or looks; showing sexual pictures, photographs, illustrations, messages or notes; writing sexual messages or graffiti on bathroom walls or locker rooms; spreading sexual rumours; calling someone gay or lesbian in a malicious manner; spying on someone dressing or showering at school; "flashing" or "mooning" someone; touching, grabbing, or pinching in a sexual way; pulling at clothing in a sexual way; intentionally brushing against someone in a sexual way; pulling clothing off or down; blocking or cornering in a sexual way; and forcing a kiss or forcing other unwelcome sexual behaviour other than kissing · (American Association of University Women, 1993; Permanent Commission on the Status of Women, 1995; Stein, Marshall & Tropp, 1993). Recent studies in the United States found that sexual harassment experienced by students in the school environment interferes with their social development and negatively impacts on their mental health and overall school performance (American Association of University Women, 1993; Permanent Commission on the Status of Women, 1995; Stein et al. (1993). To date the occurrence of sexual harassment in schools has received little attention in South Africa and most research on children in South Africa has focused on the negative effects of community violence and school violence on child mental health. All research conducted on sexual harassment in South Africa has involved university students who are adults.